Effect of Fe on microstructure, phase evolution and mechanical properties of (AlCoCrFeNi)100-xFex high entropy alloys processed by spark plasma sintering. (December 2018) - Guo, Lin; Xiao, Daihong; Wu, Wenqian; Ni, Song; Song, Min
Abstract: Understanding the alloying effect is critical for designing dual-phase high entropy alloys (HEAs). In this paper, the effects of Fe addition on microstructure, phase evolution, and mechanical properties of (AlCoCrFeNi)100-x Fex HEAs were systematically investigated. The (AlCoCrFeNi)100-x Fex (x = 5, 15, 20) HEAs were prepared by mixing Fe and AlCoCrFeNi starting powders using mechanical alloying (MA), followed by spark plasma sintering (SPS). It has been shown that all the alloys have FCC and BCC dual phase structure after consolidated by SPS. The volume fraction of FCC phase increases from 31.5% to 67.8% and the size of (Fe, Cr)-rich BCC precipitates decreases from 62 nm to 31 nm when the Fe content increases from 0 to 20 at.%. Due to the structure transformation with the increase of Fe content, the fracture strain increases from 14.9% to 29.9%, the compressive strength reduces from 1961.2 MPa to 1380 MPa and the yield strength decreases from 1702.8 MPa to 899.8 MPa. The excellent combination of strength and ductility of the HEAs is mainly ascribed to the FCC and BCC dual phase structure, and the finer nanoscale precipitates inside the BCC phase. The current investigation suggests that the good mechanical properties of dual-phase HEA can be achieved by adjusting the Fe content to further control the content and morphology of FCC and BCC phases. Graphical abstract: Highlights: The gas-atomized pre-alloy powder presents multi-grain structure with a homogeneous composition. All the sintered-specimens have FCC and BCC dual-phase structure. The addition Fe refines the microstructure, leading to a higher extent of BCC nanoprecipitation. The size of nanoprecipitates reach to ∼31 nm when the addition Fe contents increase to 20 at.%. The Fe20 alloy has a compressive yield strength of 899.8 MPa and a fracture strain of 29.9%.